Analysing vote-choice in a multinational state: national identity and territorial differentiation in the 2016 Brexit vote. Issue 9 (2nd September 2021) - Henderson, Ailsa; Poole, Ed Gareth; Jones, Richard Wyn; Wincott, Daniel; Larner, Jac; Jeffery, Charlie
ABSTRACT: Striking territorial variations in the 2016 Brexit referendum are neglected in the explanatory literature, a gap our analysis of the British Election Study (BES) helps to fill. Rather than modelling Britain as one political system, we present parallel models for England, Scotland and Wales. Typical in other multinational states, this approach is innovative for 'British politics'. The analysis shows different variables help to explain Leave support in England, Scotland and Wales. To analyse complex multilevel national identities, we develop a relative territorial identity (RTI) measure. The measure shows that those who prioritize their territorial identity in England tended to vote Leave, while the opposite is true in Wales and Scotland. The performance of this RTI measure helps to explain territorial differentiation in the 2016 Brexit vote.